Frequency of Extracranial Complications of Chronic Suppurative Otitis Media - Talukder, Md Harun Ar Rashid; Hossain, Md Monwar; Islam, Md Tariqul; Ali, Mohammad Idrish; Rahman, Mujibur; Haque, Md Momenul (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Objectives: To see the way of presentation of extracranial complication, relationship between socio-economic conditions and extracranial complication of chronic suppuration otitis media. Methods: This is a cross-sectional study carried out in Department of Otolaryngology Head and Neck Surgery, Sir Salimullah Medical College & Mitford Hospital and Dhaka Medical College Hospital from 1st July 2009 to 30th June 2010. The diagnosis was made by detailed history, clinical examination & investigation. Analyzed data was presented by various tables. Results: In this study male (59%), lower class people (57%), age 11-20 years, rural (66%) and less educated patients were more affected. Having bath in the ponds and rivers suffers more. Clinical presentation of CSOM with complications were aural discharge (100%), hearing impairment (94%), post auricular swelling (15%), pain in the ear (21%), postauricular discharge (27%) and mass in the EAC (12%). Here found aural discharge mostly malodorous and scanty, attic perforation and cholesteatoma. Post auricular abscess most common (47%) extracranial complication and labyrinthitis was the lowest (3%). Atticoantral variety was more common (89%) than that of tubotympanic disease (11%). Conclusion: From the review of the series we found the frequency & types of extracranial complications arising from CSOM and known the current epidemiological data. It can produce awareness among all level of medical practitioners and enhance prompt diagnosis and treatment. J Bangladesh Coll Phys Surg 2016; 34(1): 3-8